KAPASITAS SUMBER DAYA MANUSIA SEKSI PENDIDIKAN MADRASAH KANTOR KEMENTERIAN AGAMA KABUPATEN BANDUNG - Yusuf, Ningrum Fauziah; Sintaningrum, Sintaningrum; Utami, Sawitri Budi (Natapraja, 2019)
This study aims to look at the human resource capacity of the Ministry of Religion especially in madrasah education. This study wants to explain how the Ministry of Religion in carrying out its duties and responsibilities in the field of madrasah education includes service, guidance, guidance, management of information systems. This study uses a quantitative approach which is analyzed using analysis (Structural Equation Modeling, SEM). Data was collected by informant interviews and questionnaires. As a result, this study shows that currently the human resource capacity of the Ministry of Religion e in the madrasah education section is quite good. This can be seen from the six indicators that researchers use based on the theory of Hall, et al. (2003), which consists of quantity of employees, employee competency standards, employee motivation, reward and punnishment, skill development, and compensation. The results of the study show that in human resource capacity is strongly influenced by the dimensions of employee competency standards and compensation.